EDUKASI MULTIDISIPLIN SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN PERAWATAN STROKE PADA MASYARAKAT DESA MAYANG SUKOHARJO - Raratita Setiawan; Nisrina Firdaus; Nadia Putri Rahma Wati; Naila Najwa Ukhtufina; Denieta Rahmasari; Fildzah Alifah Nur Amalina; Radi Tia Sintia Dewi; Salsabil Salma; Almira Almira; Raisya Putri; Citranova Nurfadilla; Azzahra Putri Callista Hana; Salwa Alayda Zahrah; Sugiharto Sugiharto; Yuli Kusumawati (Universitas Muhammadiyah Surakarta, 2026)
Stroke, often caused by hypertension, is the primary focus of this community service project. Knowledge about the care of post-stroke patients is crucial, including understanding proper positioning for turning, appropriate movement exercises, personal hygiene for patients, and special diets for stroke patients. This community service activity aims to enhance the knowledge and skills of the people in Mayang Village regarding the care of post-stroke patients and to prevent complications in stroke patients. The implementation method used is a pre-experimental design with a multiple group pretest-posttest, consisting of (1) planning stage, (2) preparation stage, (3) implementation stage, and (4) evaluation stage. A quantitative approach is applied through pre-test and post-test surveys assessing the knowledge and attitudes of caregivers. The sample includes three caregivers of post-stroke patients and 17 congregants of Mushola Nur Hidayah in Mayang Village. Data were collected using questionnaires before and after educational sessions that included multidisciplinary education, simulations, and discussions. The analysis results indicate a significant improvement in the knowledge and attitudes of the people in Mayang Village regarding proper post-stroke patient care.